## lyserdoll 3 years ago 6+2 (3j-2) = 4(l+j) please show work

1. zazoo

are you asked to solve for j

2. Celeste7

In 4(1+j)or 4(l+j)

3. zazoo

what the question ask you to do

4. lyserdoll

@Celeste7 4(L+j)

5. lyserdoll

Solve forj

6. AriPotta

wouldn't you have to distribute first, then add?

7. Geometry_Hater

Are you sure that L is actually L and not a 1?

8. Celeste7

It could not be like because you will have 2 different variables l and j

9. lyserdoll

Sorry it is 1

10. Geometry_Hater

Ok just do the same thing up there just 4(l+j) would turn out to be 4+4j

11. Geometry_Hater

6+2 (3j-2) Here you actually do distribute the 2 first)......After you got all you stuff just combine like terms and then isolate j

12. Celeste7

6+2(3j-2)=4(1+j) 6+6j-4=4+4j 6j-4+6=4+4j 6j+2=4+4j 6j-4j=4-2 2j=2 J=2/2 J=1. And you can check it by replacing the answer by the variable

13. zazoo

|dw:1349821670045:dw|

14. Celeste7

15. Celeste7

I show you all the process so you did not confuse

16. mayankdevnani

any problem

17. lyserdoll

thanks

18. mayankdevnani

all right